Functional Coatings on High‐Performance Polymer Fibers for Smart Sensing. (16th February 2020) - Galinski, Henning; Leutenegger, Daniel; Amberg, Martin; Krogh, Fabio; Schnabel, Volker; Heuberger, Manfred; Spolenak, Ralph; Hegemann, Dirk
Abstract: Above a critical temperature, high‐performance fibers may lose their mechanical properties resulting in catastrophic events of damage when, e.g., used as load‐carrying ropes. Here, a method to functionalize polymer fibers with thermochromic optical coatings that enable signaling of damaging thermal history is introduced. These smart coatings are comprised of an index‐tunable anti‐reflection coating based on chalcogenide phase change materials (PCM). It is demonstrated that the insulator−metal phase transition of these materials can be aligned with the critical deterioration temperature of both polyethylene terephthalate (PET) monofilaments and liquid‐crystal polyester (LCP) yarns by composition tuning. The carefully designed optical system amplifies the change in optical properties of its constituents upon phase change. The thermal and mechanical degradation of these fibers can thus be monitored and displayed by eye. Abstract : Thermochromic optical coatings are investigated as passive sensors on high‐performance fibers to enable in‐place detection of damaging thermal exposure. The structural transformation of the optical phase change material GeSbTe results in a clearly perceptible color change when exposed to a critical temperature, which is aligned with the critical deterioration temperature of polyethylene terephthalate and Vectran fibers.